Parametric analysis CFD of the hydraulic performance of a centrifugal pump with applications to the dredging industry (2020)
The present study aims to use the analysis of CFD in a centrifugal dredge pump, to predict by mathematical correlations the effect that changes in the main variables of the dredging process would have on the behavior and efficiency of the pump. The OpenFOAM® open source software is used for the development of the study, through which a series of operating conditions that the dredging pump experiences in its operation were reproduced. The information collected from the output variables in the pump allowed us through statistical analysis, the development of mathematical correlations that allow us to directly identify the relationships between the process variables and their influence on the pump behavior (suction pressure, discharge pressure, total dynamic head, NPSHr and efficiency). The results obtained indicate that the simulation process allows a high prediction to be obtained with respect to the actual pump conditions (error below 4%). Mathematical correlations demonstrated efficiency for the operating range of work from 83% to 64%. Additionally, the NPSHr analysis allows defining operating limits that avoid adverse effects such as cavitation.